Numerical simulation study on the influence of air leakage on oxygen concentration in goafs of fully mechanized caving mining with shallow buried and large mining height - Zhu, Xingpan; Wen, Hu (Frontiers in Earth Science, 2023)
In order to reveal the influence of air leakage on oxygen concentration in goafs of fully mechanized caving mining with a shallow buried and high mining height, the air leakage of No.122108 working face in Caojiatan coal mine in different seasons was tested by the SF6 tracer gas test method. Based on the result of the air leakage test, the “three zones” of spontaneous combustion in the goaf were simulated using Ansys Fluent fluid dynamics software, and the simulated result was compared with that of the field test. The result shows that the vertical air leakage of the working face is serious, the wind speed is high, and the air leakage rate is up to 86.96%. The air leakage rate is higher in winter and lower in summer. The air leakage intensity decreases from the air inlet side to the air return side through the middle of the goaf. The range of the oxidation heating zone of the goaf is 98–245 m on the air inlet side and 33–96 m on the air return side. The numerical simulation result is well consistent with the field test data. The research conclusion can guide fire prevention and the extinguishing of No.122108 working face and lay a foundation for the prevention and control of spontaneous fire in goafs of fully mechanized caving mining with a shallow buried and high mining height.